Sociocultural communicative approach, educational quality references, and production of narrative texts (Revista Investigación & praxis en CS Sociales, 2023)
This bibliographical research was built to delve into the Sociocultural Communicative Approach and the Educational Quality References in the production of narrative texts, its general objective is to describe from the classical theorists to the avant-garde thematic implicit in the textual production and how through the time has evolved based on communicative purposes.This review allowed us to establish conclusions on the state of the matter at the national and international level, the qualitative evidence indicates that writing, its approaches and referents cross all educational levels, its study is of interest from areas such as social, cultural and academic. From the Sociocultural Approach, writing is part of the pragmatics of the language for its teaching and learning, both in the native language or first L1, as well as in a foreign or second language L2, conjecturing that oralityand writing are exercisesin cultural interaction.
Keywords: Cultural interaction; Communication process; Writing, Educational quality; Social skills